EFFECTS OF PILATES EXERCISES ON FLEXIBILITY AND VOLLEYBALL SERVE SKILL IN FEMALE COLLEGE STUDENTS - Mahnaz Manshouri; Nader Rahnama; Mojtaba Babaei Khorzoghi (Sport Scientific And Practical Aspects, 2025)
Flexibility is an important component of physical fitness which is essential to varying degrees in different sports. It becomes even more important as it not only enhances athletic efficiency but reduces the risk of injuries as well. The objective of the present study was to investigate the effects of regular Pilates exercises on flexibility and the volleyball serve skill in female, college students. For the purposes of this study, 22 female students were randomly selected and assigned to the following two groups of equal numbers: the experimental group (age: 20.64; height: 161 cm; weight: 56.27 kg) and the control (age: 20.09; height: 161.82 cm; weight: 57.18 kg). Over the six-week period of study, the experimental (Pilates) group participated in three sessions of Pilates exercises and one session of volleyball exercises each week. The control, however, participated only in the one volleyball exercise session on a weekly basis. All the subjects were tested for their flexibility and volleyball serve skills before and after the study period. The results showed that Pilates exercises had a significant effect on the subjects’ flexibility at the 0.05 probability level and improved their volleyball serve skills. Based on the results obtained from this study, Pilates exercises may be recommended for improving flexibility and sports skills.